2006
DOI: 10.2176/nmc.46.152
|View full text |Cite
|
Sign up to set email alerts
|

Pituicytoma-Two Case Reports-

Abstract: Pituicytoma is a rare tumor in the sellar or suprasellar region with distinct histological characteristics of glial neoplasm. A 42-year-old woman presented with a history of amenorrhea and vertigo, and a 62-year-old woman presented with mild headache. Both patients had mild hyperprolactinemia and one had mild anterior pituitary dysfunction. They underwent transcranial partial resection of a suprasellar tumor. The tumors were characterized by storiform pattern of elongated cells immunoreactive for S-100 protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(13 citation statements)
references
References 11 publications
1
9
0
3
Order By: Relevance
“…Depending on their state of differentiation, some pituicytomas do not express GFAP. However, ultrastructural features comparable to those described in human tumors (Nakasu et al 2006) have been previously described in pituicytoma cells positive for GFAP (Cenacchi et al 2001). These cells had features consistent with both pituicytoma and pituitary adenoma differentiation (i.e., aggregates of intermediate filaments and secretory granules), suggesting an origin of this tumor from stromal folliculostellate cells of the adenohypophysis.…”
Section: Primary Diagnostic Featuressupporting
confidence: 76%
“…Depending on their state of differentiation, some pituicytomas do not express GFAP. However, ultrastructural features comparable to those described in human tumors (Nakasu et al 2006) have been previously described in pituicytoma cells positive for GFAP (Cenacchi et al 2001). These cells had features consistent with both pituicytoma and pituitary adenoma differentiation (i.e., aggregates of intermediate filaments and secretory granules), suggesting an origin of this tumor from stromal folliculostellate cells of the adenohypophysis.…”
Section: Primary Diagnostic Featuressupporting
confidence: 76%
“…Although the neurohypophysis is associated with the storage and release of antidiuretic hormone, and is believed to be the origin of pituicytomas, only 5% of all reported cases presented with central diabetes insipidus (DI), for reasons that are unclear. 10 In our case, the patient also denied any symptoms of DI; her primary clinical presentation was Cushing syndrome.…”
Section: Discussionmentioning
confidence: 53%
“…Only one patient presented with diabetes insipidus, despite pituicytomas arising from the posterior pituitary gland or infundibulum [4]. Nakasu et al suggested that pituicytomas start to grow in the posterior lobe or lower portion of the stalk, so the upper neurohypophysis might have to compensate for the loss of function [5]. …”
Section: Discussionmentioning
confidence: 99%